Activity of Typhoons in the Spratly Archipelago (the South China Sea) - Le Mau; Vlasova Galina; Lebedev Sergey; Pham Hoan; Nguyen Dung; Nguyen Tuan; Ho The (Russian Journal of Earth Sciences, 2025)
On the basis of statistical analysis, studies of the features of the distribution of typhoons in the Spratly Archipelago (the South China Sea) for the period 1884–2020 were carried out using satellite information. As a result, it was revealed that 229 typhoons were observed over the water area of the Spratly Islands during this period. Of these, 27 had a maximum speed of over 33 m/s. A clear trend is identified towards an increasing number of typhoons, which could be a major source of regional climate risks in the future. This is probably due to the intense development of the East Asian Monsoon with a strong tropical convergence zone under current climatic conditions.